Le discours de genre dans les choix traductifs : Quelques remarques sur la scène « Les adieux d’Hector et d’Andromaque » dans l’Iliade. - Kolovou, Georgia (International Journal of Language, Translation and Intercultural Communication, 2026)
The purpose of this study is to show that the translation of a classical text into a modern language can reproduce, consciously or unconsciously, gender stereotypes. We rely on the book VI of the Iliad, and particularly on the famous scene between Andromache and Hector, and we make a linear comparison between the Greek text and the translation of four scholarly editions in French. From this textual comparison, we attempt to show that the modern translation offers the opportunity to reconsider the cultural and social norms of the epic text and to adapt them to the contemporary perspectives on the gender discourse.